Insect parasites in multicomponent systems and development of new bioinsecticides - Glupov Viktor; Martemyanov Vyacheslav; Kryukov Vadim (BIO Web of Conferences, 2020)
Stable and dynamic interactions among plants, herbivorous insects, parasites and associated microbes are formed in natural habitats. The study of these interactions in multicomponent models is required to develop integrated methods for the management of insect pest populations. In this work, we summarize our studies on the influence of different factors, such as hygrothermal conditions, host development, host microbiota, plant quality, and concomitant infections, on interactions between insects and their parasites, such as fungi, bacteria, viruses and parasitoids. Some approaches for developing complex products for biocontrol are also discussed. For example, the use of natural compounds with immunosuppressive effects may enhance the efficacy of microbial agents toward pest insects.